Respuesta :
Answer:
Subtract 9 from each side of the equation
Step-by-step explanation:
m+9=-2
-9 -9
m=-11
Answer:
the first answer is subtract 9 from each side of the equation. The second answer is m=(-11)
Step-by-step explanation:
you must set the eaquation to where the m is one side of the equation alone. to this you must subtract 9 since the nine is positive to cancel it out. what is done on one side of the equation must be done to the other.so you subtract 9 from (-2). since both are negative yo add them to get 11. (m=-11)